Influence of the technique for producing lithium-titanium ferrite ceramics on its electrical properties; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Surzhikov A. P. Anatoly Petrovich (2016, 2016)
Title screen